Monitoring Penggunaan Daya listrik Sebagai Implementasi Internet of Things Berbasis Wireless Sensor Network - Eka Putra, I Gusti Putu Mastawan; Giriantari, Ida Ayu Dwi; Jasa, Lie (Jurnal Teknologi Elektro; Vol 16 No 3 (2017): (September - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2017.v16i03p09, 2017)
One implementation of the Internet of Things (IoT) conducted in this study to realize the system of monitoring and control of electrical energy usage-based Wireless Sensor Network (WSN). This research method is the design of wireless sensor nodes that can measure the electrical parameters of alternating current (AC) as effective voltage, effective current, active power, apparent power, power factor and total electrical energy consumption by using modules ESP8266 as a liaison with a Wi-Fi. Calculation of electrical parameters obtained from ATmega328P microcontroller ADC readings of a step-down transformer that is used as a voltage sensor and sensor SCT013 used as AC current sensors will be transmitted to the server over the network from a Wi-Fi Access Point (AP). ESP8266 modules are programmed using AT-Command proven to reliably measure can transmit data simultaneously with serial data format of the wireless sensor node to a server using TCP / IP protocol. Monitoring power consumption via the internet which are designed in the research, either through the Android application and web browser proven to be reliably able to show some electrical parameters with the same data than the data logger recaps taken from SD-Card installed in the wireless sensor node.
Keywords: Internet of Things, Wireless Sensor Network, Modul ESP8266, AT-CommandModul ESP8266, AT-Command